The Everyday as Revolution and Resistance: G. Debord and M. de Certeau - Milerius, Nerijus (Problemos, 2019)
The paper analyzes the effort to rethink the status of everyday life in the context of consumer society. Two concepts of everyday life are interpreted – Guy Debord’s critique of society of the spectacle, and Michel de Certeau’s concept of everyday life as resistance. As Debord says, the purpose of the critique of the everyday is to recharge the entire system of capitalism. By capturing the radical contrast between the current meager status of everyday life and the potential of the everyday, Debord was convinced that a radical discrimination of everyday life can only be overcome by radical means – the revolution of the everyday. Rejecting the possibility of transforming the entire structure of the society through everyday life, de Certeau focused on the everyday as resistance to the strategic domains of society. Thus, de Certau’s goal is not to transform the entire system, but to maintain the resilient potential of everyday life as a constant opportunity for daily renewal. The paper concludes that it is the attitudes of everyday life such as resistance that have influenced visual and urban studies.